Method for improving underground hydrogen storage capacity by stabilizing hydrogen foam through porous carbon material

By leveraging the synergistic effect of hydrophobically modified porous carbon materials and surfactants, stable hydrogen foam was prepared, solving the problems of unstable hydrogen displacement and poor foam stability, thus achieving a significant improvement in underground hydrogen storage efficiency and efficient hydrogen extraction.

CN121180946AActive Publication Date: 2025-12-23CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202511730855.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2025-12-23
Estimated Expiration
2045-11-24

AI Technical Summary

Technical Problem

Existing underground hydrogen storage technologies suffer from several limitations, including unstable hydrogen displacement, high interfacial tension between hydrogen and formation water, poor foam stability, and the hydrophilicity of traditional porous materials, which restrict the efficiency of hydrogen storage and extraction.

Method used

By utilizing the synergistic effect of hydrophobically modified porous carbon materials and surfactants, a composite system of hydrophobically modified porous carbon materials and surfactants is prepared to form stable hydrogen foam, suppress foam disproportionation and gas-liquid separation, enhance mechanical strength, and improve flow characteristics.

Benefits of technology

It significantly improves the stability and hydrogen storage efficiency of hydrogen foam, increases the hydrogen sweep efficiency by 30-50%, achieves a recovery rate of over 80%, and extends the foam stabilization time from several hours to several days or even weeks, thereby reducing costs and realizing the high-value utilization of resources.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of underground hydrogen storage, and particularly relates to a method for improving underground hydrogen storage capacity by stabilizing hydrogen foam through a porous carbon material, which comprises the following steps: step 1, preparing a hydrophobic modified porous carbon material: preparing the porous carbon material by using biomass waste as a raw material through a carbonization-activation process; carrying out hydrophobic modification treatment on the porous carbon material to enable the water contact angle of the material to reach more than 90 degrees; step 2, preparing a surfactant solution; step 3, preparing a porous carbon-surfactant composite system; and fourthly, hydrogen foam is generated and injected, wherein hydrogen and the porous carbon-surfactant composite system are fully mixed according to the gas-liquid volume ratio of 1: 1-10: 1, and then the mixture is injected into the stratum. By means of the method, the stability of hydrogen foam can be remarkably improved, the hydrogen storage efficiency and the hydrogen recovery rate are improved, and therefore the underground hydrogen storage amount is greatly increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of underground hydrogen storage technology, specifically relating to a method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity. Background Technology

[0002] Hydrogen, as a clean, efficient, and renewable secondary energy source, has become an important strategic development direction for the transition from fossil fuels to new energy sources. However, there is a significant spatial and temporal mismatch between hydrogen supply and consumption. Hydrogen production from wind and solar power exhibits significant regional and seasonal variations, while end-use applications of hydrogen require a continuous and stable supply. Underground hydrogen storage technology, by utilizing underground structural space to achieve large-scale, high-pressure storage of hydrogen, is an important means to solve the problem of the spatial and temporal mismatch between hydrogen production and consumption.

[0003] However, existing underground hydrogen storage technologies face the following technical challenges: 1. Hydrogen instability displacement problem: The low viscosity (0.0089 mPa·s at 25℃ and 0.1MPa) and low density (0.082 kg / m³) of hydrogen make it prone to viscous fingering and gravity differentiation in the formation, which significantly reduces the sweep efficiency and production efficiency of hydrogen in the reservoir.

[0004] 2. Low hydrogen replacement efficiency: The interfacial tension between hydrogen and formation water is relatively large, which limits its ability to replace and drive formation water, resulting in limited formation hydrogen storage capacity.

[0005] 3. Poor foam stability: Although hydrogen foam technology can improve the flow characteristics of hydrogen, the thermodynamic instability of hydrogen foam under high-temperature formation conditions severely restricts its application effectiveness. Factors such as foam disproportionation and gas-liquid separation cause the foam structure to break down rapidly, making it impossible to maintain hydrogen storage efficiency in the long term.

[0006] 4. Limitations of material hydrophilicity: Traditional porous materials are rich in hydrophilic functional groups on their surface, which can easily adsorb formation water under formation conditions, reducing the adsorption capacity for hydrogen. At the same time, hydrophilic particles are difficult to adsorb stably at the gas-liquid interface, which weakens the foam stability enhancement effect.

[0007] Therefore, developing a new method that can effectively stabilize hydrogen foam and improve the efficiency of underground hydrogen storage has important theoretical and practical value. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a method for stabilizing hydrogen foam with porous carbon materials to improve underground hydrogen storage. Through the synergistic effect of hydrophobically modified porous carbon materials and surfactants, the stability of hydrogen foam is significantly enhanced, thereby substantially improving underground hydrogen storage efficiency. The specific technical means are as follows: A method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity includes the following steps: Step 1: Preparation of hydrophobically modified porous carbon materials: (1) Using biomass waste (such as agricultural and forestry waste, straw, sawdust, etc.) as raw materials, porous carbon materials are prepared by carbonization-activation process; in the carbonization-activation process, carbonization is carried out in a nitrogen atmosphere at a carbonization temperature of 450~800℃ and a carbonization time of 1~4h, and activation is carried out by CO2 or KOH at a carbonization temperature of 700~900℃ and an activation time of 0.5~3h. (2) Hydrophobic modification treatment is carried out on porous carbon materials by chemical vapor deposition, silane coupling agent grafting or high temperature heat treatment to remove hydrophilic functional groups (such as -OH, -COOH, etc.) on the surface of the material so that the water contact angle of the material reaches more than 90°. The prepared hydrophobically modified porous carbon materials have a micropore content (<2nm) of 60-80% and a specific surface area of ​​800-2000m². 2 / g; Step 2: Prepare the surfactant solution: (1) Select anionic surfactants (such as sodium dodecyl sulfate SDS, sodium dodecylbenzene sulfonate SDBS) or nonionic surfactants (such as polyoxyethylene ethers); (2) Prepare an aqueous solution of surfactant with a concentration of 0.1~2.0 wt%, preferably 0.5~1.0 wt%; Step 3: Preparation of porous carbon-surfactant composite system: (1) Disperse the hydrophobically modified porous carbon material in an aqueous surfactant solution; (2) The hydrophobic modified porous carbon material is uniformly dispersed by ultrasonic dispersion or high-speed stirring to form a stable suspension, which is the porous carbon-surfactant composite system. The concentration of the hydrophobic modified porous carbon material in the porous carbon-surfactant composite system is 0.5~5.0wt%, preferably 1.0~3.0wt%. During the dispersion process, the hydrophobic carbon chains of surfactant molecules interact with the hydrophobically modified porous carbon surface through van der Waals forces, and the hydrophilic head groups extend into the aqueous phase, forming an interfacial molecular self-assembly structure of "hydrophobic embedding-hydrophilic extension". Step 4: Generation and Injection of Hydrogen Foam: (1) Hydrogen gas is mixed with a porous carbon-surfactant composite system at a gas-liquid volume ratio of 1:1 to 10:1, preferably at a gas-liquid volume ratio of 3:1 to 5:1. (2) By using a foam generator or an online mixing device, hydrogen is fully mixed with the composite system to generate hydrogen foam containing porous carbon particles; (3) Inject into the formation. Preferably, the injection pressure is controlled to be 0.5~5.0 MPa higher than the formation pressure, and the injection rate is 0.1~10.0 m. 3 / h; Step 5: Control of underground hydrogen storage process: (1) During the hydrogen storage period, based on the formation pressure monitoring results or changes in hydrogen production, a porous carbon-surfactant composite system is injected to maintain foam stability. (2) During the extraction stage, a slow depressurization method is adopted, and the extraction rate is controlled at 30% of the injection rate to ensure efficient hydrogen recovery.

[0009] The technical principle of this invention is based on the following synergistic mechanism: 1. Suppressing foam disproportionation: The microporous structure of hydrophobically modified porous carbon provides a large number of physical adsorption sites for hydrogen molecules. At the same time, the hydrophobic carbon chains of surfactants interact with hydrogen molecules, building an energy barrier on the bubble surface, effectively suppressing the transmembrane migration of hydrogen.

[0010] 2. Inhibition of gas-liquid separation: The physical adsorption of hydrogen by porous carbon materials reduces the gas phase diffusion rate. At the same time, porous carbon particles form a network of physical barriers on the liquid film surface, increasing the liquid phase flow resistance and slowing down the gas-liquid separation process.

[0011] 3. Enhanced mechanical strength: Porous carbon particles encapsulate bubbles to form a solid-liquid-gas three-phase foam, providing skeletal support and increasing the mechanical strength of the bubbles, making them less prone to collapse under external disturbances.

[0012] 4. Improved flow characteristics: Foam significantly increases the apparent viscosity of hydrogen, inhibiting viscous fingering; increases the apparent density of hydrogen, reducing gravitational differentiation; reduces gas-liquid interfacial tension, and improves displacement efficiency.

[0013] Beneficial effects Compared with the prior art, the present invention has the following advantages: 1. Significantly improves foam stability: The synergistic effect of hydrophobic modified porous carbon materials and surfactants extends the stability time of hydrogen foam under formation conditions from several hours to several days or even weeks.

[0014] 2. Significantly improve hydrogen storage efficiency: By suppressing viscous fingering and gravity differentiation, the sweep efficiency of hydrogen in the reservoir is increased by 30-50%; by reducing interfacial tension, the efficiency of hydrogen replacing formation water is increased by 40-60%.

[0015] 3. Improve hydrogen recovery rate: Foam reduces the diffusion capacity of hydrogen in the formation and forms a high-density foam area near the injection and production wells, which can achieve a hydrogen recovery rate of over 80%.

[0016] 4. Wide range of raw material sources: Porous carbon materials are prepared from biomass waste, realizing high-value utilization of resources, low cost, and environmental friendliness.

[0017] 5. Simple and controllable operation: The process is simple, the parameters are adjustable, and it is easy to implement on site and apply on a large scale. Detailed Implementation

[0018] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not serve to limit it in any way.

[0019] The reagents used in the embodiments and comparative examples of this invention are all commercially available products. In the embodiments and comparative examples of this invention, various performance parameters were tested according to the following methods: Example 1 This embodiment discloses a method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage, including the following steps: Step 1: Preparation of hydrophobically modified porous carbon materials: The straw was carbonized at 600℃ in a nitrogen atmosphere for 2 hours, and then activated with CO2 at 800℃ for 1 hour to obtain porous carbon material. By using chemical vapor deposition, trimethylchlorosilane vapor was introduced at 400°C for 2 hours to achieve a water contact angle of 120° for porous carbon materials. The resulting hydrophobically modified porous carbon material has a specific surface area of ​​1200 m² / g and a micropore ratio of 75%.

[0020] Step 2: Prepare the surfactant solution: Prepare a 0.8 wt% SDS solution; Step 3: Preparation of porous carbon-surfactant composite system: The hydrophobic modified porous carbon material prepared in step one was dispersed in the surfactant solution prepared in step two and ultrasonically dispersed for 30 minutes. In the porous carbon-surfactant composite system, the concentration of the hydrophobic modified porous carbon material was 2.0 wt%.

[0021] Step 4: Generation and Injection of Hydrogen Foam: Hydrogen and a porous carbon-surfactant composite system were mixed in a 4:1 ratio to generate foam, which was then injected into the reservoir.

[0022] Example 2 This embodiment discloses a method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage, including the following steps: Step 1: Preparation of hydrophobically modified porous carbon materials: Wood chips were carbonized at 500℃ in a nitrogen atmosphere for 3 hours, and then activated with KOH at 800℃ for 2 hours to obtain porous carbon materials. Surface grafting with octadecyltrichlorosilane and reaction in n-hexane at 80°C for 6 hours resulted in a water contact angle of 135°. The resulting hydrophobically modified porous carbon material has a specific surface area of ​​1500 m² / g and a micropore content of 70%.

[0023] Step 2: Prepare the surfactant solution: Prepare a 1.0 wt% SDBS solution; Step 3: Preparation of porous carbon-surfactant composite system: The hydrophobic modified porous carbon material prepared in step one was dispersed in the surfactant solution prepared in step two and ultrasonically dispersed for 30 minutes. In the porous carbon-surfactant composite system, the concentration of the hydrophobic modified porous carbon material was 1.5 wt%.

[0024] Step 4: Generation and Injection of Hydrogen Foam: Hydrogen and a porous carbon-surfactant composite system were mixed in a 3:1 ratio to generate foam, which was then injected into the reservoir.

[0025] Comparative Example 1 A method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity, which differs from Example 1 in that hydrophobically modified porous carbon materials are not prepared, specifically including the following steps: Step 1: Prepare the surfactant solution: Prepare a 0.8 wt% SDS solution; Step 2: Generation and Injection of Hydrogen Foam: Hydrogen gas and surfactant solution are mixed in a 4:1 ratio to generate foam, which is then injected into the reservoir.

[0026] Comparative Example 2 A method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity, which differs from Example 2 in that hydrophobically modified porous carbon materials are not prepared, specifically including the following steps: Step 1: Prepare the surfactant solution: Prepare a 1.0 wt% SDBS solution; Step 2: Generation and Injection of Hydrogen Foam: Hydrogen gas and surfactant solution are mixed in a 3:1 ratio to generate foam, which is then injected into the reservoir.

[0027] Comparative Example 3 A method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity, which differs from Example 1 in that the porous carbon material is not modified, specifically includes the following steps: Step 1: Preparation of porous carbon materials: The straw was carbonized at 600℃ in a nitrogen atmosphere for 2 hours, and then activated with CO2 at 800℃ for 1 hour to obtain a porous carbon material with a water contact angle of 25°. Step 2: Prepare the surfactant solution: Prepare a 0.8 wt% SDS solution; Step 3: Preparation of porous carbon-surfactant composite system: The porous carbon material prepared in step one was dispersed in the surfactant solution prepared in step two and ultrasonically dispersed for 30 minutes. In the porous carbon-surfactant composite system, the concentration of the porous carbon material was 2.0 wt%.

[0028] Step 4: Generation and Injection of Hydrogen Foam: Hydrogen and a porous carbon-surfactant composite system were mixed in a 4:1 ratio to generate foam, which was then injected into the reservoir.

[0029] Results Test The sweep efficiency, recovery rate, displacement efficiency, and foam stabilization time of the hydrogen foam prepared in Examples 1-2 and Comparative Examples 1-3 were tested. The sweep efficiency, recovery rate, and displacement efficiency were determined by core displacement experiments, and the foam stabilization time was determined under simulated formation conditions (using a high-pressure visualization device under formation conditions).

[0030] The results show: The hydrogen foam prepared in Example 1 has a hydrogen sweep efficiency of 80%, a foam stabilization time extended to 10 days, an extraction rate of 85%, and a hydrogen replacement efficiency of 65%.

[0031] The hydrogen foam prepared in Comparative Example 1 had a hydrogen sweep efficiency of 55%, a foam stabilization time of 2 days, a extraction rate of 62%, and a hydrogen replacement efficiency of 40%.

[0032] The results above show that, compared with the hydrogen foam of Comparative Example 1 using surfactant alone, the hydrogen sweep efficiency of Example 1 was increased by 45%. The hydrogen foam prepared in Example 2 showed a 55% improvement in hydrogen replacement efficiency compared to the hydrogen foam in Comparative Example 2 using a surfactant alone (40% in Comparative Example 2 → 62% in Example 2). The foam stability time exceeded 15 days, while the foam stability time in Comparative Example 2 was 2 days. The hydrogen sweep efficiency of Example 2 was 82.5%, and the extraction rate reached 88%.

[0033] The hydrogen foam prepared in Comparative Example 3 had a hydrogen sweep efficiency of 66%, a recovery rate of 70%, a hydrogen replacement efficiency of 48%, and a foam stabilization time of 4 days. Although the hydrogen sweep efficiency was improved by 20% compared to Comparative Example 1, and other properties were also improved, compared to the hydrogen foam prepared in Example 1, the sweep efficiency, recovery rate, replacement efficiency, and foam stabilization time decreased by 17.5%, 17.6%, 26.2%, and 60%, respectively, indicating that the effect was significantly worse than that of Example 1.

[0034] Therefore, the preparation method disclosed in this invention can significantly improve hydrogen storage efficiency, increase hydrogen extraction rate, and enhance foam stability.

Claims

1. A method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage, characterized in that, Includes the following steps: Step 1: Preparation of hydrophobically modified porous carbon materials: Porous carbon materials are prepared using biomass waste as raw material through a carbonization-activation process; The porous carbon material is hydrophobically modified so that the water contact angle of the material reaches more than 90°. Step 2: Prepare the surfactant solution: Prepare an aqueous solution of anionic or nonionic surfactants with a concentration of 0.1-2.0 wt%. Step 3: Preparation of porous carbon-surfactant composite system: Hydrophobic modified porous carbon material was uniformly dispersed in an aqueous surfactant solution to obtain a porous carbon-surfactant composite system, wherein the concentration of the hydrophobic modified porous carbon material in the porous carbon-surfactant composite system was 0.5~5.0 wt%. Step 4: Generation and Injection of Hydrogen Foam: Hydrogen and porous carbon-surfactant composite system are thoroughly mixed at a gas-liquid volume ratio of 1:1 to 10:1 and then injected into the formation.

2. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, In step one, the carbonization-activation process is as follows: carbonization is carried out in a nitrogen atmosphere at a temperature of 450~800℃ for 1~4h, followed by activation with CO2 or KOH at a temperature of 700~900℃ for 0.5~3h.

3. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, In step one, the hydrophobic modification treatment is carried out by chemical vapor deposition, silane coupling agent grafting, or high-temperature heat treatment.

4. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, In step two, the anionic surfactant is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate; the nonionic surfactant is polyoxyethylene ether.

5. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, In step four, the specific conditions for injection into the formation are as follows: the injection pressure is controlled to be 0.5~5.0 MPa higher than the formation pressure, and the injection rate is 0.1~10.0 m / s. 3 / h.

6. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, It also includes the following steps: Step 5: Control of underground hydrogen storage process: During the hydrogen storage period, based on the formation pressure monitoring results or changes in hydrogen production, a porous carbon-surfactant composite system is injected to maintain foam stability. During the extraction phase, a slow depressurization method is adopted, and the extraction rate is controlled at 30% of the injection rate.

7. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, In step two, the concentration of the surfactant aqueous solution is 0.5~1.0wt%.

8. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, In step three, the concentration of hydrophobic modified porous carbon material in the porous carbon-surfactant composite system is 1.0~3.0 wt%.

9. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, In step four, the gas-liquid volume ratio of the hydrogen and porous carbon-surfactant composite system is 3:1 to 5:

1.

10. The method for stabilizing hydrogen foam with porous carbon materials to increase underground hydrogen storage capacity according to claim 1, characterized in that, The biomass waste refers to agricultural and forestry waste, straw, or wood chips.

Citation Information

Patent Citations

  • Carbon-based foam nanocomposite hydrogen storage material

    CN101375449A

  • Green reinforced foam system for underground hydrogen storage and preparation method thereof

    CN116119609A

  • Method and device for increasing weight hydrogen storage amount of hydrogen hydrate

    CN116216632A

  • Aerogel-surfactant nanofluid system, preparation method and application thereof, and method for improving formation gas storage amount

    CN118879292A

  • CO2 flooding and improving system suitable for water-sensitive stratum and implementation method of CO2 flooding and improving system

    CN119062291A

Cited By

  • Preparation system and application of nano bubble liquid

    CN121648768A

  • A nano-bubble liquid preparation system and application

    CN121648768B